KONSEP KEBEBASAN ALBERT CAMUS DALAM TINJAUAN FILSAFAT PENDIDIKAN: RELEVANSINYA DENGAN PENDIDIKAN DI INDONESIA - , GLORIA RAHMA GINTING ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Freedom is crucial in all areas of human life and it has been recognized since the time of the pre-Socratic era. The definition of freedom have been developed, but many issues that arise related to freedom, so people need a appropriate understanding of freedom. The title of this research is âAlbert Camusâ Concept of Freedom in The Philosophy of Education Perspective : Its Relevance to Education in Indonesia\\". The purpose of this thesis is to explore Albert Camusâ thought of freedom from the viewpoint of Educational Philosophy of Existentialism. Freedom is absolutely a very important thing in human life, and has been discussed since pre-ancient Greece until present. This is a library research using Albert Camusâ thought as material object and philosophy of education as formal object. This research uses verstehen, interpretation, Hermeneuticâs, and Heuristicsâ methods. These methods are used to explore the further concept about freedom according to Albert Camusâs thought, which will be reviewed from the perspective of existentialist philosophy of education. Therefore, this research will obtain the concept of freedom by Albert Camus and wil find its relevant to education in Indonesia. The results from this research are : first, the philosophy of existentialism education strongly emphasizes the importance of freedom in education. The freedom means courteous and responsibility. This educational philosophy considers that freedom is an essential thing in education in order to develope studentâs talent and potential, thus the student will grow to be an adaptable and able to face life challenges. Second, Humans are in a world full of contradictions and it is a sign of absurdity. Consciousness of absurdity is the first step to the realization of human freedom, that is responsible and uphold the justice. Third, Albert Camusâ thought about the absurdity and freedom can be the basis for an existentialist educators in educating their students. Albert Camus thought of freedom is very useful when applied in the world of education, because it can help students to think creatively. In addition, it can help students to realize and to develop their own potential. Albert Camusâ thought can be actualized in curriculum planning, the role of teachers to students and students to teachers as well. Fourth, Albert Camusâ thought about the absurdity and freedom can be applied in the education in Indonesia by using mutatis mutandis and eclectic incorporative approach, in order to align with values of Pancasila. Albert Camus' thought about education can be used to evoke the spirit of education \\"soul\\" in Indonesia.